Pengaruh Program Acara â€œFamily 100â€ MNCTV Terhadap Minat Menonton: Survei Pada Ibu- Ibu RW 04 Kelurahan Bojongsari, Kota Depok - Novielda Rahmadania; Mulkan Habibi (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
The â€œFamily 100â€ program was broadcast on MNCTV. After going through several rounds and getting high scores on survey questions, the team will struggle to get tens of millions of rupiah in prize money. The aim of this research is to evaluate how MNCTV's â€œFamily 100â€ program influences viewers' attention. The Event Program bases its operations on the theories of Format Power, Star Power, and Information Power. Cognitive, Affective and Conative are the next elements that are interesting to pay attention to. This research uses a quantitative survey methodology. Questionnaires were distributed as part of the data collection process. uses probability sampling techniques to take samples. To produce accurate results, the data obtained was then processed using SPSS version 29. With tcount (5.872) > ttable (1.992), it can be concluded that the MNCTV "Family 100" program has a significant effect on viewing interest. The percentage of program viewing that influences viewing interest is 79.9%, and the remaining 20.1% is influenced by other factors.